2020
DOI: 10.1049/hve.2019.0116
|View full text |Cite
|
Sign up to set email alerts
|

PVC nanocomposites for cable insulation with enhanced dielectric properties, partial discharge resistance and mechanical performance

Abstract: The current study aims to develop polyvinyl chloride (PVC) nanocomposites with enhanced electrical and mechanical properties by incorporating titanium oxide (TiO2) nanoparticles within PVC chains. Different loading of nanoparticles and different nanoparticle surface states were considered. The surface states are unfunctionalised, functionalised using vinyl silane and functionalised using amino silane. The choice of a most suitable surface state was a critical factor that guarantees a good dispersion of nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…In future work, the application of nanotechnology for enhancing the breakdown voltage strength of various insulating materials [44][45][46][47][48][49][50][51][52] in the presence of different barrier effects will be investigated, specifically in the transformer insulating oil.…”
Section: Discussionmentioning
confidence: 99%
“…In future work, the application of nanotechnology for enhancing the breakdown voltage strength of various insulating materials [44][45][46][47][48][49][50][51][52] in the presence of different barrier effects will be investigated, specifically in the transformer insulating oil.…”
Section: Discussionmentioning
confidence: 99%
“…In the other hand, PVC/MB nanocomposite micrograph in Figure 4-b show remarkable low amount of bentonite aggregates at the surface. The dense distribution of raw bentonite in Figure 4-a can be revealed as a result of the incompatibility between PVC and bentonite particles (Abdel-Gawad, et al, 2020), but in the case of PVC/MB nanocomposite, the bentonite aggregates seem to be incorporated with PVC due to the increase of compatibility between them.…”
Section: Scanning Electron Microscope Semmentioning
confidence: 99%
“…On the contrary, the gradual addition of surfacemodified bentonite as filler to PVC composites shows accompanied gradual decrease to the resulted PVC/MB nanocomposites until equal 5.86 ×Ω•cm after addition 10 phr of MB. This gradual decrease in volume resistivity of PVC/ MB nanocomposites can be revealed as result of the presence of surfactant material (Giancoli, 1995;Abdel-Gawad, et al, 2020).…”
Section: Characterization Of Electrical Propertiesmentioning
confidence: 99%
“…Many experimental studies of the breakdown strength of nanocomposites have been reported [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. In most cases, the measurements were carried out under a uniform electric field or semi-uniform electric field using sphere-to-sphere electrode or sphere-to-plane electrode, respectively, as shown in Figure 3 .…”
Section: Dielectric Properties Of Polymer Nanocompositesmentioning
confidence: 99%